2014
DOI: 10.1890/13-2248.1
|View full text |Cite
|
Sign up to set email alerts
|

Planktonic larval mortality rates are lower than widely expected

Abstract: TitlePlanktonic larval mortality rates are lower than widely expected Abstract. Fundamental knowledge of mortality during the planktonic phase of the typical marine life cycle is essential to understanding population dynamics and managing marine resources. However, estimating larval mortality is extremely challenging, because the fate of microscopic larvae cannot be tracked as they develop for weeks in ocean currents. We used a two-pronged approach to provide reliable estimates of larval mortality: (1) frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 64 publications
1
39
0
Order By: Relevance
“…Moreover, the ability of larvae to regulate transport could have a large impact on dispersal and population connectivity and has been debated for decades. We recently determined that larvae occurred close to shore in persistent, strong upwelling on the Pacific Coast of the USA-rather than lost offshore as was widely expected (Morgan et al, 2009b(Morgan et al, ,c, 2011Morgan and Fisher, 2010;Fisher et al, 2014;Hameed et al, 2018)-and that larval mortality in the nearshore retention zone was much lower than previous estimates of larval mortality anywhere (White et al, 2014). We then demonstrated that larval behaviors enabling larvae to remain close to shore throughout development also enable them to settle near natal populations (Drake et al, 2013;Hameed et al, 2016).…”
Section: Introductionmentioning
confidence: 63%
“…Moreover, the ability of larvae to regulate transport could have a large impact on dispersal and population connectivity and has been debated for decades. We recently determined that larvae occurred close to shore in persistent, strong upwelling on the Pacific Coast of the USA-rather than lost offshore as was widely expected (Morgan et al, 2009b(Morgan et al, ,c, 2011Morgan and Fisher, 2010;Fisher et al, 2014;Hameed et al, 2018)-and that larval mortality in the nearshore retention zone was much lower than previous estimates of larval mortality anywhere (White et al, 2014). We then demonstrated that larval behaviors enabling larvae to remain close to shore throughout development also enable them to settle near natal populations (Drake et al, 2013;Hameed et al, 2016).…”
Section: Introductionmentioning
confidence: 63%
“…Better estimates of dispersal and connectivity in the 572 deep sea will require more details about larval behavior and development at depth. In 573 addition, spatial variation in fecundity, mortality during the larval phase and larval 574 physiological tolerance needs to be included because they can influence dispersal and 575 population connectivity (Treml et al, 2012;White et al, 2014). …”
Section: Caveats 543mentioning
confidence: 99%
“…One important consideration is that the mortality rate estimated by White et al [49] explicitly accounts for and excludes advection, while the observed settlement data include mortality as well as losses due to advection, which may contribute significantly to the mortality of open-coast invertebrate larvae [64]. By projecting the consequences of our dispersal kernel for metapopulation dynamics, we estimated the predicted connectivity among all subpopulations in the study.…”
Section: Discussionmentioning
confidence: 99%